Hubungan Pendidikan Agama Kristen dan Budi Pekerti dengan Etika Kepribadian Siswa Siswi Kelas VII SMP Negeri 4 Balige Kabupaten Toba Tahun 2024 - Debora Gerizim Sitompul; Dorlan Naibaho; Ordekoria Saragih; Boho Parulian Pardede; Rawatri Sitanggang (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Christian Religious Education and Ethics is the government's effort through education to have a good impact on students' personality ethics. However, in the development of today's times, the ethics of students' personalities are getting worse so that they cause deviations. That is what makes the author feel interested and encouraged to conduct research on the relationship between Christian Religious Education and Ethics with the personality ethics of SMP Negeri 4 Balige students in 2024. This study aims to determine the relationship between Christian Religious Education and Ethics with the personality ethics of students in grade VIII of SMP Negeri 4 Balige in 2024. The research method used is a quantitative approach with inferential statistical data analysis. The population in this study is all grade VIII students of SMP Negeri 4 Balige which totals 208 students consisting of seven classes. Sampling in this study uses the probability sampling technique, which provides the same opportunity for each population to be selected as a sample member. The sample of this study was 62 people. The results of the research obtained using the r test are r_(count) > r_(table), which is 0.658 > 0.254 and the t-test t_(count) > t_(table), which is 6.769 > 2,000, it shows that there is a strong, positive and significant relationship between Christian Religious Education and Ethics and the personality ethics of students in grade VIII of SMP Negeri 4 Balige in 2024. In the determination coefficient test, data results of 43.3% were obtained which could be explained by Christian Religious Education and Ethics, while 56.7% were explained by other variables that were not researched by the researcher. This study is a recommendation for future researchers to research other variables related to student personality ethics using research methods and data collection tools that are more optimal.